Excellent Classroom Management: Strategies for Improving Academic and Non-Academic Achievement at Islamic Junior High School - Zakia Min Fadlillah; Eti Hadiati; Sela Kholidiani (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Optimally enhancing student potential requires planned and systematic classroom management. At MTs Negeri 1 Bandar Lampung, there is a challenge to integrate superior class management to be able to boost student achievement comprehensively, both in terms of intellectual and character. This study aims to describe the superior class management strategy in improving academic and non-academic achievement of students at MTs Negeri 1 Bandar Lampung. This study uses a qualitative approach with a case study method. Data were collected through interview techniques, observation, and documentation. Research informants included the principal, vice principal, teachers, and students to gain a comprehensive perspective. The research findings indicate that superior class management is implemented through four main stages: (1) planning a directed learning program, (2) organizing resources according to competencies, (3) implementing innovative learning, and (4) controlling through continuous evaluation and supervision. This implementation has been proven to have a positive impact on improving learning outcomes and competitive achievements (academic), as well as strengthening discipline, self-confidence, and developing student talents and interests (non-academic). This study provides a practical contribution to educational institution managers regarding the importance of systematic special class management as a model for improving graduate quality. In addition, this study strengthens the theory of educational management regarding the effectiveness of organizing resources in the school environment.